Country-level analysis of household fuel transitions. (February 2019) - McLean, Elena V.; Bagchi-Sen, Sharmistha; Atkinson, John D.; Ravenscroft, Julia; Hewner, Sharon; Schindel, Alexandra
Highlights: Population density and size, and charcoal production are associated with greater solid fuel use in households. Urbanization and greater income equality are associated with reduced solid fuel dependence. GDP per capita, electricity and gas production are also associated with reduced solid fuel dependence. GDP per capita has a strong association with a declining trend in solid fuel use. Governments' renewable energy incentives are associated with reduced dependence on solid fuels. Abstract: Solid fuel combustion remains a dominant energy source for household heating and cooking in less developed countries. As a result, almost three billion people are exposed to household air pollution, causing four million premature deaths annually, primarily among poor women and children. We analyze data from Demographic and Health Surveys in 69 countries to identify determinants of transition from solid to cleaner fuel. Estimates from a population-averaged linear model show that population density and size, rural population share, income inequality, and charcoal production are positively associated with countries' solid fuel use, while GDP per capita, electricity and natural gas production have the opposite effect. Economic development, measured as GDP per capita, has the strongest link to solid fuel use: a standard deviation increase in per capita GDP above its mean reduces solid fuel use from 70% to 57% of households. Electricity production is another strong predictor: solid fuel use drops by 11% when electricity production increases by one standard deviation above the mean. In addition, in a fixed-effects linear model, population size has a positive association with solid fuel use, while increases in GDP per capita and the number of governments' renewable energy incentives are associated with lower dependence on solid fuels.